Tax risk management in the public control in order to ensure the tax security of the state - K. V. Maslov (Правоприменение, 2025)
The subject. The norms of Russian legislation governing risk management systems in the implementation of various types of public control.The purpose of the study is to confirm or refute the hypothesis that different types of public controls affect the tax security of the state, and tax risk management systems should be coordinated in their implementation.Methodology. The author uses methods of system analysis of scientific papers devoted to the various types of public control. Formal logical and legal interpretation of Russian regulatory legal acts is used also.The main results. The impact of tax, customs, currency control, AML/CFT control and other types of public control on ensuring the tax security of the state is substantiated. The interrelation of the existing tax risk management systems of the state in Russia in the implementation of these types of control is revealed.Conclusions. It is necessary to uniformly fix the basic principles of risk management in the regulations governing the grounds and procedures for such public control, ensuring tax security of the state. These principles include: the obligation to identify, assess, and systematize risks and other threats, describe indicators, categorize management objects accordingly, and correlate adopted regulatory and individual legal acts with the goals of preventing the occurrence and/or minimizing of the harmful effects of a particular risk or threat.